2007
DOI: 10.1111/j.1468-1293.2007.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and ethnicity impact on the maximum proliferative response in peripheral blood lymphocytes from HIV‐seropositive individuals

Abstract: SummaryThe effects of race and ethnicity on immunological function have not been fully studied in patients infected with HIV-1. To study such differences, 54 patients on virally suppressive highly active antiretroviral therapy (HAART) with CD4 counts 4200 cells/mL had their peripheral blood lymphocytes (PBL) evaluated for response to recall antigen. Significant differences were found in the maximum responses for PBL from black individuals compared with those from white individuals, and the differences were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Our study showed a poorer CD4+ response for non-whites. Studies have shown that neutropenia is more common in Blacks than Whites [30], although the proliferative response to recall antigen of peripheral blood lymphocytes may be greater in Blacks than Whites [31]. Again, adherence may play a role in the differences by race found in our study [29].…”
Section: Discussionmentioning
confidence: 39%
“…Our study showed a poorer CD4+ response for non-whites. Studies have shown that neutropenia is more common in Blacks than Whites [30], although the proliferative response to recall antigen of peripheral blood lymphocytes may be greater in Blacks than Whites [31]. Again, adherence may play a role in the differences by race found in our study [29].…”
Section: Discussionmentioning
confidence: 39%
“…T-cell proliferation in response to HCV was more frequent and targeted more viral proteins in adult African-Americans than in Caucasians [ 28 ], and HCV-specific T cells from Caucasians expressed higher levels of the inhibitory molecule PD-1 [ 29 ]. A study on HIV-infected patients on suppressive HAART conducted in the United States reported that black patients had stronger proliferative T-cell responses to fungi than white individuals [ 30 ]. Among patients with pulmonary tuberculosis followed up in the United Kingdom, those of African ancestry produced larger amounts of inflammatory mediators in response to Mycobacterium tuberculosis antigens than those of Eurasian ancestry [ 31 ].…”
Section: Discussionmentioning
confidence: 99%